Nalar Fikih Fatwa Nahdlatul Ulama Tentang Bisnis Multi Level Marketing (Studi Munas Alim Ulama NU tahun 2019) - Pratama, Frisma (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
Multi Level Marketing which is abbreviated as MLM has experienced rapid development, this business is one of the direct selling which is engaged in the trade in goods or services, however, the provisions of Islamic law regarding this business often have pros and cons whether it is allowed or not. The Islamic organization Nahdlatul Ulama has a view on this business, namely through the bahtsul masail forum which was published in Bahtsul Masail's decision on MLM business law discussed at the 2019 NU Alim Ulama National Conference. the fiqh reasoning used by Bahtsul Masail in determining the MLM business law. The results of the study, the authors concluded, namely: First, Bahtsul Masail NU stated two decisions, namely that there were MLM businesses that were not allowed and those that were allowed. Not allowed, Bahtsul Masail thinks that MLM business is all the same, Bathsul Masail looks at the price of the product above the market price to attract customers to want to register to become members so they can get cheaper prices, in that way, they are sellers can have a network Underneath, their motivation is not profit selling but the bonuses they get when they can recruit as many people as possible. This is allowed, because basically the MLM system is muamalah or buyu’ whose basic principle is permissible (permissible) as long as there is no element of Riba, Ghoror (unclearness), Dhoror (harming or harming other parties), Jahalah (not transparent). Second, the fiqh reasoning used is using “contextual social fiqh reasoning”. By using the istinbath method of qauliy and manhajiy laws. The qauly method is a form of selective (critical) ijtihad. The Manhajy method is to take the methodology used by the scholars of the past and ushul fiqh and qawa'id fiqhiyyah.